2015
DOI: 10.4314/ijbcs.v9i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary limnological survey of Ori stream, Iwo, Osun State, Nigeria

Abstract: Ori stream (one of the tributaries of River Oba, Iwo, Osun State, Nigeria) was studied from October to December 2013 with the aim of providing baseline information on its water quality, phytoplankton primary productivity and invertebrate faunal composition. Plankton samples were collected by towing plankton net over a 2 metres horizontal distance, while benthic macroinvertebrate samples were collected by kick-sampling technique. Hydrological and some physico-chemical variables were determined in-situ, and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Also, some PEs reported in this study were below those obtained in a study conducted byOlutona and Dawodu (2016), who identi ed and quanti ed PEs in water and sediment of Ori stream, Iwo, Southwestern Nigeria. The disparity might have resulted from environmental conditions and factors surrounding the sources of water samples used in this study, which are also in line with the ndings ofAkindele et al (2015). The values observed for concentrations of some PCB congeners, including 153 and 180 in the 0-5.6 ppm range, agree with the ndings ofZhang et al (2007), who also reported that most PCBs were undetected.Health risk associated with PCBs and PEs in adults and children through ingestion route Tables 7, 8, and 9 show variations in the health risks associated with PCBs and PEs at the three locations in line with hazard quotient/non-carcinogenic risk (HQ) and incremental life carcinogenic risk (ILCR).…”
supporting
confidence: 87%
“…Also, some PEs reported in this study were below those obtained in a study conducted byOlutona and Dawodu (2016), who identi ed and quanti ed PEs in water and sediment of Ori stream, Iwo, Southwestern Nigeria. The disparity might have resulted from environmental conditions and factors surrounding the sources of water samples used in this study, which are also in line with the ndings ofAkindele et al (2015). The values observed for concentrations of some PCB congeners, including 153 and 180 in the 0-5.6 ppm range, agree with the ndings ofZhang et al (2007), who also reported that most PCBs were undetected.Health risk associated with PCBs and PEs in adults and children through ingestion route Tables 7, 8, and 9 show variations in the health risks associated with PCBs and PEs at the three locations in line with hazard quotient/non-carcinogenic risk (HQ) and incremental life carcinogenic risk (ILCR).…”
supporting
confidence: 87%
“…It has been reported that the environmental condition of the Ori stream continues to degrade with the ever expanding population of Iwo (Akindele et al, 2015). This study is the first to be conducted on the occurrence of PAEs in water and sediments in this area.…”
Section: Introductionmentioning
confidence: 90%
“…Unlike Aiba stream, the stream is situated along the outskirt part of the town but various developmental projects have extended to the area. Due to the rising human needs, a lot of activities such as open markets, motor parks, abattoir, irrigation farming activities, car wash, filling stations, technical school and spiritual bathing taking place along the course of the stream has led the stream to be subjected to various eutrophic, disruptive and thermal stress as it flows through the city and empty itself into Oba river (Akindele et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…In fish, gills are critical organs for their respiratory, osmoregulatory, and excretory functions (Ezemonye and Ogbomida, 2010). Gills are considered good indicators of water quality, being models for studies of environmental impact, since they are the primary route for the entry of chemicals (Akindele et al, 2015). Gills are the major respiratory organs and all metabolic pathways depend upon the efficiency of the gills for their energy supply.…”
Section: Histopathological Examinationsmentioning
confidence: 99%